2010
DOI: 10.1098/rstb.2009.0261
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal dynamics and spermatogenesis

Abstract: Different cellular events occur during spermatogenesis, and these include (i) mitosis for self-renewal of spermatogonia, (ii) differentiation of type A spermatogonia into type B and commitment of type B spermatogonia to develop into preleptotene primary spermatocytes, (iii) transit of preleptotene/ leptotene spermatocytes across the blood -testis barrier in coordination with germ cell cycle progression and meiosis, (iv) spermiogenesis and spermiation. These events also associate with extensive changes in cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 108 publications
1
120
0
2
Order By: Relevance
“…[13][14][15] Thus, it is conceivable that there is extensive junction restructuring taking place at the cellcell interface, involving constant remodeling of the cytoskeleton to facilitate these events. [16][17][18] Interestingly, the basal ES which is found at the Sertoli-Sertoli cell interface at the site of the BTB and the apical ES which is restricted to the Sertoli cellspermatid (from step 8-19 spermatids in rats) interface, share similar ultrastructural features, that is, actin filament bundles sandwiched in between cisternae of endoplasmic reticulum and the apposing Sertoli cell or Sertoli cell-spermatid plasma membranes. 1,16,18 Earlier studies have shown that these actin filament (F-actin) bundles are maintained by actin bundling and capping proteins [e.g., epidermal growth factor receptor pathway substrate 8 (Eps8)], 19 and actin nucleation proteins [e.g., actinrelated protein 3 (Arp3) of the Arp2/3 complex].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…[13][14][15] Thus, it is conceivable that there is extensive junction restructuring taking place at the cellcell interface, involving constant remodeling of the cytoskeleton to facilitate these events. [16][17][18] Interestingly, the basal ES which is found at the Sertoli-Sertoli cell interface at the site of the BTB and the apical ES which is restricted to the Sertoli cellspermatid (from step 8-19 spermatids in rats) interface, share similar ultrastructural features, that is, actin filament bundles sandwiched in between cisternae of endoplasmic reticulum and the apposing Sertoli cell or Sertoli cell-spermatid plasma membranes. 1,16,18 Earlier studies have shown that these actin filament (F-actin) bundles are maintained by actin bundling and capping proteins [e.g., epidermal growth factor receptor pathway substrate 8 (Eps8)], 19 and actin nucleation proteins [e.g., actinrelated protein 3 (Arp3) of the Arp2/3 complex].…”
Section: Resultsmentioning
confidence: 88%
“…[16][17][18] Interestingly, the basal ES which is found at the Sertoli-Sertoli cell interface at the site of the BTB and the apical ES which is restricted to the Sertoli cellspermatid (from step 8-19 spermatids in rats) interface, share similar ultrastructural features, that is, actin filament bundles sandwiched in between cisternae of endoplasmic reticulum and the apposing Sertoli cell or Sertoli cell-spermatid plasma membranes. 1,16,18 Earlier studies have shown that these actin filament (F-actin) bundles are maintained by actin bundling and capping proteins [e.g., epidermal growth factor receptor pathway substrate 8 (Eps8)], 19 and actin nucleation proteins [e.g., actinrelated protein 3 (Arp3) of the Arp2/3 complex]. 20 Interestingly, these actin-associated proteins are also known to participate in endocytic vesicle-mediated trafficking at the cell-cell interface to "stabilize" or "de-stabilize" cell adhesion protein complexes, facilitating spermatid movement.…”
Section: Resultsmentioning
confidence: 88%
“…54,55 They therefore could not present the exogenous constriction force, and so the precise function remains controversial. 13 Autophagy is active in Sertoli cells, [26][27][28][29] and early morphology studies found that the lysosomes of the seminiferous epithelium show cyclical variations.…”
Section: Discussionmentioning
confidence: 99%
“…F-actin is packed in hexagonal arrays in the ES, while it appears as a branched network surrounding the tubular portion of TBCs. 43,55 As PDLIM1 could work as a scaffold to recruit other molecules to bind the F-actin bundles, and the binding of PDLIM1 to ACTN1 and PALLD may offer more actin binding site in a smaller volume, facilitating the F-actin interconnectivity, 9,60,61 so the accumulation of PDLIM1 may facilitate the branched F-actin network formation in TBCs rather than affecting their assembly. The disordered distribution of TBCs might be caused by the abnormal structure of apical ES or malformed sperm head, and these possibilities still need further experimental data to be distinguished in the future.…”
Section: Discussionmentioning
confidence: 99%
“…1). As noted above, virtually all the proteins that are involved in these processes have been identified in the testis during the past decade and localized to the apical and basal ES at sites where actin filament bundles are present, 52,53 illustrating that they are involved in actin remodeling to facilitate spermiogenesis.…”
Section: Introductionmentioning
confidence: 99%